"Relato do estágio profissional de uma futura Professora: uma busca permanente pelo desenvolvimento profissional e pessoal" - Beatriz Isabel Vilaça Simões (2022)
The supervised teaching practice allows the student trainee to have a real experience of teaching Physical Education in schools accompanied by specialized and experienced professionals, a cooperator at the school level, and a faculty advisor. This document is called a School Placement Report and intends to describe the professional practice of a preservice teacher during her school placement for an entire school year. Where all the knowledge acquired during the first year of the degree was put into practice until now: a year full of learning, adaptations, and enriching experiences. This path is presented here, reporting on the strategies implemented, the premise of distributed practice, and the proactive accountability of students in the learning process. Fortunately, unrelated to the previous confinements, this year was more similar to the normality previously known and, thus, the classes were solely face-to-face. This allowed me to experience and develop strategies to involve students in the teaching-learning process in a distributed practice. Particular importance is also given to adaptive competence which stimulated the attempt to develop the ability to adapt the teaching-learning process to the individuality of the student through study. I end with a reflection of my enriching experience and the desire to embrace this very fulfilling profession.